TRANSPARANSI GAJI DAN KESETARAAN PENGUPAHAN: TREN BARU DALA KEADILAN KOMPENSASI - Shalahuddin; Nerys Lourensius L. Tarigan (Program Studi Manajemen, 2026)
Salary transparency and pay equity have become central issues in human resource management due to increasing demands for compensation fairness, organizational accountability, and the reduction of gender-based pay gaps. This article aims to examine the concepts, theoretical foundations, empirical evidence, and managerial implications of salary transparency as an instrument of compensation justice. This study applies a conceptual literature review of reputable academic articles, international reports, and recent regulations related to pay transparency. The review shows that salary transparency is not limited to disclosing pay amounts; it also includes openness in compensation processes, job criteria, salary ranges, pay gap audits, and corrective mechanisms for pay inequity. Recent studies indicate that salary transparency can reduce gender pay gaps, strengthen perceptions of organizational justice, and improve employer accountability. However, its effectiveness depends on policy design, data quality, public accessibility of information, and organizational readiness to correct pay structures. Salary transparency without job evaluation systems, compensation communication, and corrective mechanisms may create resistance, social comparison conflict, or unproductive pay compression. This article recommends a gradual approach through compensation audits, job-based pay structures, communication of pay criteria, gender pay gap reporting, and data-driven corrective actions.